2021
DOI: 10.2147/opto.s324187
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Hysteresis in Thais and Variation of Corneal Hysteresis in Glaucoma

Abstract: Purpose To collect the normal value data of corneal hysteresis in Thais and study the variation of corneal hysteresis in glaucomatous eyes. Methods Retrospective cross-sectional study of corneal hysteresis (CH) in healthy non-glaucomatous and glaucomatous eyes. Demographic data, type and staging of glaucoma, Goldmann applanation tonometry (GAT) and ocular response analyzer parameters; CH, corneal-compensated intraocular pressure (IOPcc) and Goldmann-correlated intraocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…The current study revealed comparative values (10.02 and 9.18 mmHg for control and treated POAG eyes, respectively). CH was significantly lower in the treated POAG group, as previously reported 9 , 50 . However, no significant difference was observed in CH between the control and treatment-naïve POAG groups, with the AUC value as low as 0.59.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current study revealed comparative values (10.02 and 9.18 mmHg for control and treated POAG eyes, respectively). CH was significantly lower in the treated POAG group, as previously reported 9 , 50 . However, no significant difference was observed in CH between the control and treatment-naïve POAG groups, with the AUC value as low as 0.59.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies indicated that CH measured with ORA is useful when diagnosing 9 , monitoring the development 10 , and conducting management 12,13 of glaucoma. Many studies have reported CH in normative (9.77-10.20 mmHg) [49][50][51] and also treated glaucomatous eyes (7.5-9.5 mmHg) [12][13][14]35 . The current study revealed comparative values (10.02 and 9.18 mmHg for control and treated POAG eyes, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the mean CH in the POAG-HTG severe stage was 7.92 mmHg compared to 9.22 mmHg in the early stage and 8.74 in the moderate stage (p < 0.001). In PACG, the mean CH was statistically significantly lower in the severe stage (8.45) compared to the early stage (9.85) (p = 0.004) but not when compared to the moderate stage (9.04, p = 0.2) [71]. In contrast, in a study of 49 patients, Yang and colleagues compared the CH in POAG-HTG versus POAG-NTG and reported no significant difference (10.11 mmHg versus 10.17 mmHg, respectively) (p = 0.81) [77].…”
Section: Clinical Studies Measuring Corneal Hysteresis and Corneal Re...mentioning
confidence: 81%